Religion as Source Domain of Metaphors in World War II Media Discourse - O. A. Solopova; N. N. Koshkarova (Научный диалог)
The article studies the English-language media discourses of the World War II period from a retrospective point of view. The aim is to identify the patterns of modeling the images of war and peace in British, American and Australian media discourses. The definition of military media discourse as an institutional form of communication is proposed, its essential characteristics are highlighted. The source of the material was the authoritative digitized archives of the UK, the USA and Australia. The material was extracted using corpus linguistics tools. The qualitative analysis was carried out within the framework of the cognitive-discourse methodology using the method of metaphorical modeling. The object of the research is the dominant metaphor used when representing the images of war and peace in the three discourses. The authors show common and specific features of the use of the religious metaphor, conditioned by cultural and extra-linguistic factors, and conclude that the religious metaphor places war and peace at different poles of the scale of values and actualizes the binary axiological opposition “good — evil”, “light — darkness”.